Dual metal-free polymer reactive sites for the efficient degradation of diclofenac by visible light-driven oxygen reduction to superoxide radical and hydrogen peroxide. Issue 8 (28th June 2019) - Zhang, Qianxin; Tan, Cuiwen; Zheng, Xiaoshan; Chen, Ping; Zhuo, Meihui; Chen, Tiansheng; Xie, Zhijie; Wang, Fengliang; Liu, Haijin; Liu, Yang; Zhang, Xiangdan; Lv, Wenying; et al.
Abstract : Hydrogen peroxide (H2 O2 ) and superoxide radical (O2 ˙ − ) play a critical role in environmental remediation technologies. Abstract : Hydrogen peroxide (H2 O2 ) and superoxide radical (O2 ˙ − ) play a critical role in environmental remediation technologies. Here, we report on metal-free co-catalysts with the in situ incorporation of carbon dots (CDs) into a polymeric O and N co-linked carbon nitride (OCN) framework, which significantly enhanced the synthesis of H2 O2 and O2 ˙ − due to dual reactive sites. For the photocatalytic degradation of a typical pharmaceutical and personal care product (PPCP), CDs/OCN demonstrated excellent photocatalytic performance in contrast to g-C3 N4 and OCN, which was 11.6 times that of pure g-C3 N4 . The trapping experiment has shown that O2 ˙ − plays an important role in the degradation of DCF. CDs/OCN exhibited higher electron–hole separation efficiencies than g-C3 N4 and OCN, as the result of the excellent transfer and storage performance of the CDs. The yield of H2 O2 generation by CDs/OCN was higher than that by g-C3 N4 and OCN. Meanwhile, the electron paramagnetic resonance (EPR) spectra revealed that additional O2 ˙ − and ˙OH were generated via the CDs/OCN system. Density functional theory (DFT) and Raman spectroscopy analyses revealed the presence of CD/OCN-resident dual reactive sites, which had distinct selective oxygen reduction capacities. We observed that O2 was more prone to 2-electron reduction on OCN, whereas O2 was more easily reduced to O2 ˙ − on the surface of CDs through the additional e − provided by OCN. This study clearly demonstrates a simple strategy for the design and synthesis of metal-free materials in the preparation of H2 O2 and O2 ˙ − toward the degradation of organic pollutants.